# 9.

5

Complex variables

1. Consider the function u + iv = f ( z) where
⎧ x 3(1 − i) − y 3(1 − i)
,

x2 + y2
f ( z) = ⎨

0
,

z ≠0

f ( z) = u + jv is

z =0

for this function two statements are as follows:
at the origin.

The correct statement are
(C) Both 1 & 2

(D) neither 1 nor 2

e
in

g
n

2. If f ( z) = u + iv , then consider the four solution for

E
O

∂v
∂v
−i
∂y
∂x

o
D

a
a

∂u
∂v
(4)
−i
∂y
∂y

The correct solution for f ′ ( z) are

F

(C) 1 & 3

2

(B) 3 & 4

3. If f ( s) = x + iy , then f ′ ( z) exist at all points on the
line
(A) x = y

(B) x = − y

(C) x = 2 + y

(D) y = x + 2

4. The conjugate of the function u = 2 x(1 − y) is
2

2

(C) x − y − 2 y + c

8. If v =

(D) z −3 + c

x− y
, then analytic function f ( z) = u + iv is
x2 + y2
(B) z −1 + c

(A) z + c
(C) (1 − i)

1
+c
z

9. If u =

sin 2 x
, then the analytic function
cosh 2 y − cos 2 x

(D) (1 + i)

1
+c
z

f ( z) = u + iv is
(A) cot z + ic

(B) cosec z + ic

(C) sinh z + ic

(D) cosh z + ic

10. The integration of f ( z) = x 2 + ixy from A(1, 1) to
B(2, 4) along the straight line AB joining the two
points is
−29
(A)
+ i11
3
(C)

23
+ i6
5

11.

∫ ( z + 1) 4

(B) x 2 − y 2 + 2 y + c
(D) None of the above

5. If f ( z) = u + iv is an analytic function of z = x + iy and
(B) e − z + (1 + i) c

e2 z

(B)

29
− i11
3

(D)

23
− i6
5

dz = ? where c is the circle of z = 3

c

(A)

4πi −3
e
9

(B)

4πi 3
e
9

(C)

4πi −1
e
3

(D)

8πi −2
e
3

v − v = e x (cos y − sin y), the f ( z) in terms of z is
(A) e − z + (1 + i) c

(B) z −2 + c

(D) 2 & 4

2

(A) x 2 + y 2 − 2 y + c

r
e

(C) z 3 + c

(B) only 2

(A) 1 & 2

(B) cosh z + ic

(D) sinh −1 z + ic

(C) sinh z + ic

(A) z 2 + c

(A) only 1

∂u
∂v
(3)
−i
∂x
∂x

.c
s

(A) cosh −1 z + ic

7. If v = 2 xy , then the analytic function f ( z) = u + iv is

Statement 2 : f ′(0) does not exist

(2)

m
o

6. If u = sinh x cos y then the analytic function

Statement 1 : f ( z) satisfy Cauch–Riemann equation

f ′ ( z)
∂u
∂u
(1)
−i
∂x
∂x

(D) e −2 z + (1 + i) c

(C) e z + (1 + i) c

The value of . 1718: a a 3z 2 + 7 z + 1 f ( z0 ) = ∫ dz . f ( z) = sin z about z = 2 m o (C) 2 ⎤ ⎛ π⎞ 1 ⎛ π⎞ 1 ⎡ ⎢1 − ⎜ z − ⎟ − ⎜ z − ⎟ − ...... 3 2 sin πz (A) z =3 c (A) i6π (C) i4π (D) 0 2 ⎤ ⎛ π⎞ 1 ⎛ π⎞ 1 ⎡ ⎢1 + ⎜ z − ⎟ − ⎜ z − ⎟ − ... f ( z) = n =1 z −1 about the points z = 0 z +1 Expand the function 1 in Laurent’s ( z − 1)( z − 2) series for the condition given in question.... 19..⎥ 4⎠ 2!⎝ 4⎠ 2⎣ ⎝ ⎢ ⎥ ⎦ 2 ⎤ ⎛ π⎞ 1 ⎛ π⎞ 1 ⎡ ⎢1 + ⎜ z − ⎟ + ⎜ z − ⎟ + ..c s 21..) (B) −1 − 2( z − z 2 + z 3.⎥ 4⎠ 2!⎝ 4⎠ 2⎣ ⎝ ⎢ ⎥ ⎦ e in (B) i2π g n 1 cos πz dz around a rectangle 2πi ∫ z 2 − 1 c E O with vertices at 2 ± i ...... −2 ± i is (A) 6 (B) i2 e o D (C) 8 (D) 0 Statement for Q. then z −2 is equal to ∞ (A) 1 + ∑ ( n + 1)( z + 1) n −1 n =1 ∞ (B) 1 + ∑ ( n + 1)( z + 1) n + 1 n =1 ∞ (C) 1 + ∑ n( z + 1) n n =1 17.. Complex variables 1 − 2z ∫ z( z − 1)( z − 2) dz = ? where c is the circle z = 15 .) (C) −1 + 2( z − z 2 + z 3.. where c is the circle ( z − z0 ) c F x 2 + y 2 = 4.⎥ 2 ⎣ ⎦ (D) −3 2 (B) ⎤ 1⎡ 1 1 2 ⎢1 − 2 ( z − 1) + 2 2 ( z − 1) ..... 23..⎥ 4⎠ 2!⎝ 4⎠ 2⎣ ⎝ ⎢ ⎥ ⎦ (D) None of the above 22......... 1 < z < 2 1 2 3 (A) + 2 + 3 + ..... c (A) 2 + i 6π (B) 4 + i 3π (C) 1 + iπ (D) i3π (A) 1 + 2( z + z 2 + z 3. 18... f ( z) = 1 about z = 1 z +1 (B) 2 3 (A) ⎤ 1 1 −1 ⎡ 2 ⎢1 − 2 ( z − 1) + 2 2 ( z − 1) . r e π 4 (B) ∫ ( z − 2)( z − 1) dz = ? where c is the circle 16... The value of f ( 3) is ∞ (A) 6 (B) 4i (C) −4i (D) 1 + ∑ ( n + 1)( z + 1) n (D) 0 Statement for Q..5 20.... The value of f ′(1 − i) is (A) 7 (π + i2) (B) 6 (2 + iπ ) (C) 2π (5 + i13) (D) 0 Statement for 19–21: Expand the given function in Taylor’s series.. ∫ dz = ? where c is the circle z = 3 c z −1 (C) ⎤ 1⎡ 1 1 2 ⎢1 + 2 ( z − 1) + 2 2 ( z − 1) ... If z + 1 < 1... ∫ ( z − z 2 ) dz = ? where c is the upper half of the circle c z =1 −2 (A) 3 Chap 9..528 12... z z z (B) K − z −3 − z −2 − z −1 − 1 1 1 1 3 − z − z2 − z −K 2 4 8 18 .⎥ 2⎣ ⎦ cos πz 14....⎥ 2⎣ ⎦ (A) i2 π (B) − i2 π (D) None of the above (C) i6 π 2 (D) − i6 π 2 (C) 15. 23–25.) (D) None of the above 13..

.. The Laurent’s series of f ( z) = (B) i3 π (B) − 6π 1 1 1 1 2 + + 6z + z + . ∫ z(1 − z)( z − 2) dz = ? where c is (D) 3 z 1 3 z + + + ..... 2π 3 (D) −2π 3 x2 ∫ ( x 2 + a 2 )( x 2 + b2 ) dx = ? −∞ (A) π ab a+b (B) π ( a + b) ab (C) π a+b (D) π ( a + b) ... z < 1 1 2 1 3 7 15 3 + z + z2 + z ....c s 1 − 2z c (D) None of the above (C) 1 at z = 0 is z −1 (B) 2 (A) 2 (C) 2 3 +7 2 15 2 z + z . 2 2 4 8 (D) None of the above 1 − e Zz at its pole is z4 −4 (B) 3 29. z z z 1 8 13 (B) + 2 + 3 + ..... 2 4 16 64 z cos z dz = ? where c is z − 1 = 1 π⎞ ⎜z − ⎟ 2⎠ ⎝ ∫⎛ (D) None of the above 1 1 1 1 2 − + − z + .. ( z + 1)( z 2 + 4) 2 z = 15 ......... 2! 5! E O (C) − ( z − 1) − ( z − 1) 3 − ( z − 1) 5 − .... If z − 1 < 1 .. z > 2 6 13 20 (A) + 2 + 3 + .... 1 ∫ z 2 e dz = ? where c is z z =1 (A) i3π (B) − i3π iπ C) 3 (D) None of the above (C) 1 1 1 1 2 + + z2 + z + ..5 (C) Complex variables 1 3 7 2 + 2 + 4 ....................................... the Laurent’s series for 1 is z( z − 1)( z − 2) g n ( z − 1) 3 ( z − 1) 5 − − ... 4 4 8 16 26.. The Laurent’s series of a a e in (C) 2 32............. 2 4 8 c c 34. z 2 2 z 12 720 where z < 1 1 5 3 21 5 (A) z − z + z .. ( z − 1) 3 ( z − 1) 5 (A) − ( z − 1) − − − ......... 2 4 8 16 (C) 1 3 31. z z z 2 3 4 (D) 2 − 3 + 4 − ..... 720 z 12 634 (A) 1 3 15 5 z − z3 + z ....... The residue of the function 24.. o D 27..... z z z (D) 529 1 1 2 3 4 15 6 + z + z + z ....Chap 9............ (D) − ( z − 1) −1 − ( z − 1) − ( z − 1) 3 − ( z − 1) 5 − .... 1 1 5 4 21 6 (B) + z 2 + z + z ..... z z z (A) 4 3 1 3 7 (C) 2 + 3 + 4 + .... 2! 5! (B) − ( z − 1) −1 − r e (A) − i3π 1 for z < 2 is z( e z − 1) 33. 2 4 (A) 1 + 3z (B) (D) ∞ 35. 4 16 64 (D) −2 (C) i2π (B) 28........... 2 + 2 z 12 720 z 2π dθ ∫ 2 + cos θ = ? 0 −2π (B) 2 (C) 2π 2 (D) None of the above z is..... The residue of z cos 25.... (A) 6 π (A) F m o −1 3 ..... z z z (C) −2 3 30.....

it does not depends on the path along which Δz → 0.. . f ′( z) = *************** Now..530 Complex variables ∞ ⎡ x 3 + i( x 3) 1 ⎤ f ′ (0) = lim ⎢ ⎥=1+ i 2 x →0 x⎦ ⎣ (x ) dx 36. Again. F Δy = 0 ∴ Δz → 0 Now equation (1) Δu + iΔv Δu Δv f ′( z) = lim = lim + i lim Δx →0 Δx →0 Δx Δx →0 Δx Δx ∂u ∂v . x + y2 ⇒ x3 + y3 v= 2 x + y2 0 we get . so we apply first principle method..(2) f ′( z) = +i ∂x ∂x ∂u ∂y ∂v ∂v By differentiation the value of at(0. 0) h3 h2 = lim = lim =1 h →0 ∂x h →0 h h a a ∂v v(0. ∫ 1 + x6 = ? 0 (A) π 6 (B) 2π (C) 3 π 2 So we see that f ′(0) is not unique.(1) Δz →0 Δx + iΔy 2.H.(3) ∂y ∂y Δy →0 Now.(1) ∂x ∂y .. 0) − k3 k2 = lim = lim = −1 k →0 ∂v h →0 k k o D ∂v v(0 + h. f ′(0) = lim ⇒ r e g n At the origin. (C) Since.e. f ( z) = u + iv Here u = x 2 and v = y 2 ∂u ∂u Now.. then ⎡ ( x 3 − y 3) + i( x 3 + y 3) 1 ⎤ f ′ (0) = lim⎢ ⎥ z →0 ( x2 + y2 ) ( x + iy) ⎦ ⎣ 2i 1+ i = 2(1 + i) 2 Again let z → 0 along y = 0. ∂x ∂y ∂x ∂y Thus. 0 + k). 0) .. (A) Since. we see that m o Let Δz → 0 along a path parallel to real axi Cauchy Riemann equations are ∂u ∂v ∂u ∂v and = =− ∂x ∂y ∂y ∂x = Chap 9. of equation (2) and (3) must be same i.. .. Cauchy-Riemann equations are satisfied at z →0 f ( z) − f (0) z ⎡ ( x 3 − y 3) + i( x 3 + y 3) 1 ⎤ = lim ⎢ ⎥ 2 2 z →0 (x + y ) ( x + iy) ⎦ ⎣ Now let z → 0 along y = x. then Δx → 0 .5 ∂u ∂u ∂v ∂v −i = +i ∂x ∂y ∂y ∂x 3. z ≠0 x2 + y2 ⇒ x3 − y3 u= 2 . 0) − v(0. the derivative f ′( z) exits of the limit in equation Solutions (1) is unique i.S. x 3(1 + i) − y 3(1 − i) 1. 0) h3 h2 = lim = lim = 1 h →0 h →0 ∂x h h ∂u u(0. Hence f ′(0) does not exist. 0) k3 k2 = lim = lim =1 k →0 ∂y k →0 k k ∂u ∂v ∂u ∂v and = =− ∂x ∂y ∂y ∂x Hence. for existence of f ′( z) R... then Δx → 0 and Δz → 0 → Δy → 0 Thus from equation (1) Δz + iΔv φ ′( z) = lim Δy →0 iΔy = lim Δu Δv ∂u ∂v + i lim = + Δy →0 iΔz iΔy i∂y ∂y f ′( z) = −i∂u ∂v + .c s e in Again. let Δz → 0 along a path parallel to imaginary axis. 0) − u(0.. ∂u ∂v ∂v ∂u +i = −i ∂x ∂x ∂y ∂y ∂u ∂v ∂v −∂u and = = ∂x ∂y ∂x ∂y f ′( z) = z = 0. 0 + k) − u(0. u = x 2 ⇒ = 2 x and =0 ∂x ∂y and v = y 2 ⇒ ∂v ∂v = 0 and =2y ∂x ∂y we know that ∂u ∂u f ′( z) = − i . (A) Given f ( z) = x 2 + iy 2 since. π (D) 3 df Δf = lim dz Δz →0 Δz Δu + iΔv Or f ′( z) = lim . 0 E O ∂u u(0 + h. f ( z) = u + iv = ..e. v(0..

(B) 531 . Now. 0) = cosh z − i ⋅ 0 = cosh z .... y) ∂y by Milne’s Method On integrating f ( z) = sinh z + constant ⇒ .. y). 0) = − 9..e. (A) = e x (sin y + cos y) dx + e x (cos y − sin y) dy x 8. whatever be the path of reaching at that point From equation (3) and (4) 2 x = 2 y Hence.. f ′( z) exists for all points lie on the line x = y.. U = ( u − v)..5 and f ′( z) = Complex variables ∂v ∂v + i . y) ( x2 + y2 )2 ∂v ( x 2 + y 2 ) − ( x − y)2 x y 2 − x 2 + 2 xy = = = h( x...(3) ..(2) g n E O if ( z) = −v + iu add equation (1) and (2) o D ⇒ (1 + i) f ( z) = ( u − v) + i( u + v) ⇒ F ( z) = U + iV where.(1) ⇒ . 0) − iψ( z. ∂u ∂ u = 2(1 − y) . for existence of f ′( z) at any point is necessary that the value of f ′( z) most be unique at that point...... Thus u is harmonic. 0) 2 cos 2 z − 2 −2 = − i(0) = = − cosec2 z 1 − cos 2 z (1 − cos 2 z) 2 On integrating .(2) m o f ( z) = w = sinh z + ic (As u does not contain any constant. y) ∂x ∂y Now let v be the conjugate of u then ∂v ∂v ∂u ∂u dv = dx + dy = − dx + dy ∂x ∂y ∂y ∂x by Milne’s Method (by Cauchy-Riemann equation) f ′( z) = g( z. y) (cosh 2 y − cos 2 y) 2 ∂u 2 sin 2 x sinh 2 y = = ψ( x. 0) + ih( z. 0) = 2 z + i 0 = 2 z ⇒ 7. ∂v ∂v = 2 y = h( x...(4) Now... 0) − iψ( z. ∂x 2 ∂y 2 ⇒ f ( z) = e z + (1 + i) c f ′( z) = φ ( z. U = u − v = e (cos y − sin y) ∂U = e x (cos y − sin y) ∂x ∂U and = e x (− sin y − cos y) ∂y F Now. 0) + ih( z. y) ∂x ∂u and = − sinh x sin y = ψ( x. the constant c is ∂2u ∂2u + = 0.. = 2 x = g( x.. V = u + v a a Let F ( z) be an analytic function.(3) ∂y ∂x x + iy e in On integrating f ( z) = z 2 + c 2 On integrating v = x − y + 2 y + C x r e (1 + i) f ( z) = (1 + i) e + ic1 i i(1 − i) c = e z + c1 ⇒ f ( z) = e z + 1+ i 1 (1 + i)(1 − i) = ∂u 2 cos 2 x (cosh 2 y − cos 2 x) − 2 sin 2 2 x = ∂x (cosh 2 y − cos 2 x) 2 2 cos 2 x cosh 2 y − 2 = φ ( x. equation (1) gives f ′( z) = 2 x and equation (2) gives f ′( z) = 2 y ⇒ . F ( z) = (1 + i) f ( z). (A) dv = 2 x dx + 2(1 − y) dy 2 5.. y) ∂y (cosh 2 y − cos 2 x) 2 By Milne’s Method f ′( z) = φ ( z. y) ∂x ( x2 + y2 )2 ( x2 + y2 )2 By Milne’s Method f ′( z) = g( z. (D) ⎛ 1⎞ 1 1 ⎜ ⎟ 2 + i − 2 = − (1 + i) 2 z z ⎝ z ⎠ On integrating 1 1 f ( z) = (1 + i) ∫ 2 dz + c = (1 + i) + c z z −∂U ∂U dx + dy. 2 = 0 ∂y ∂y ( i + 1) c1 2 6. 2 = 0 ∂x ∂x ∂u = cosh x cos y = φ ( x.(2) ∂y ∂x = ez + Now.c s in the function x and hence i.(1) ∂u ∂2u = −2 x . dV = x = d[ e (sin y + cos y)] on integrating V = e x (sin y + cos y) + c1 x F ( z) = U + iV = e (cos y − sin y) + ie (sin y + cos y) + ic1 = e x (cos y + i sin y) + ie x (cos y + i sin y) + ic1 F ( z) = (1 + i) e z + ic1 = (1 + i) e + ic1 z = ∂v −( x 2 + y 2 ) − ( x − y)2 y = ∂y ( x2 + y2 )2 y 2 − x 2 − 2 xy = g( x. (C) Given f ( z) = u + i v . in w).Chap 9.. (C) u = sinh x cos y 2 4.

. and z = 2 + 4 i corresponding to t = 1 Formula then. y = d b = 1.5 1 − 2z f ( z) = − ∫ cosec2 z dz + ic = cot z + ic ∫ z( z − 1)( z − 2) dz 1 3 I1 + I 2 − I 3.. c = 3 dx = dt ..532 Complex variables Chap 9. z o = 1. 4 = c + 1 ⇒ a = 1.. so the function f ( z) is analytic . therefore by Cauchy’s integral .(2) 3 Now. z = 1 + i and On B. z = 2 + 4 i 1 ∫ z dz and it c Let z = 1 + i corresponds to t = 0 lies inside z = 15.... f ( z) is analytic within and on z = 3 e dz z = 8πi − z e 3 12. ∫ = f ′′( z o) ( z − z o) 4 3 c .. c 13. now by Cauchy’s integral formula f ( z o) = 1 2πi f ( z) ∫z−z c o dz ⇒ ∫ c f ( z) dz = 2πif ( z o) z − zo take f ( z) = cos πz..(3) Since. therefore I 2 = 2πi. and z o = −1 in (1).(3) . y = c + d 2 = a + 1. f ( z) = e ⇒ ⇒ f ′′′(−1) = 8 e f ′′′( z) = 8 e .c s everywhere in c i. x = at + b.(2) Similarly..e..(4) z −2 π e 2 z dz e 2 z dz Given fc =∫ ( z + 1) 4 c [ z − (−1)]4 ∫ ( z + 1) 4 = e in I3 = ∫ g n 2πi n f ( z o) n! r e theorem 11. (4) in (1). t = 0 I1 = ∫ ⇒ ⇒ x = b. (B) Given contour c is the circle z = 1 ⇒ z = e iθ dz = ie iθdθ ⇒ Now. d = 1 and t = 1 ⇒ ⇒ c AB is . z = 15. y = ct + d Since. (B) Let f ( z) = cos πz then f ( z) is analytic within and If is the circle z = 3 4 = ∫ | | 3 ( z + 1) 3 −2 e 2 z dz 8πi ∫ ( z + 1) 4 = 3 e−2 c 2z 1 ⎤ 2 1⎡1 1 = i ⋅ ⎢ ⋅ ( e 2 πi − 1) − ( e 3πx − 1) ⎥ = i ⎣2 3 ⎦ 3 2z equation (2) have ⇒ 1 − 2z ∫ z( z − 1)( z − 2) dz = 2 (2πi) + 2πi − 2 (0) = 3πi c F 2z using equations (2). for I 2 = ∫ c 2 1 dz = 2πi z 1 − 2z 1 1 3 = + − z( z − 1)( z − 2) 2 z z − 1 2( z − 2) on z = 3.(1) 2 2 = c 10. + i( t + 1)( 3t + 1)][ dt + 3i dt ] t= 0 c f ( z) dz ⎤ ⎥ [Here f ( z) = 1 = f ( z o) and z o = 0] z − zo ⎦ c 1 = ∫ . hence by Cauchy’s integral . y = 3t + 1 ⇒ ∫ f ( z) dz = ∫ ( x c 2 ⎡ 1 ⎢ f ( z o) = 2πi ⎣ x = a + b. we have ∫3 z= cos πz dz = 2πif (1) = 2πi cos π = −2πi z −1 15.. 0 ≤ θ ≤ π iθ − e 2 iθ) ie iθdθ θ= π π ⎡ e 2 iθ e 3iθ ⎤ − = i ∫ ( e 2 iθ − e 3iθ)dθ = i ⎢ ⎥ 3i ⎦0 ⎣ 2i 0 14. we have e 2 z dz c 1 dz = 0.. dy = 3 dt + ixy)( dx + idy) ∫ [( t + 1) For I 3 = ∫ c 1 0 f ( z) dz o c n +1 = E O o D f ( z) dz πi Taking n = 3. 1 ⎡ t3 ⎤ 29 = (1 + 3i)⎢ + t 2 + t + i( t 3 + 2 t 2 + t) ⎥ = − + 1 1i 3 ⎣3 ⎦0 ∫ (z − z ) m o 1 dz.... for upper half of the circle... the singular point z = 1 lies z −1 inside z = 15. z = 0 is the only singularity for I1 = On A.(1) a a c πi f ′′′(−1).. (D) We know by the derivative of an analytic function that n! f ( z) dz f ′′( z o) = 2πi ∫ ( z − z o) n + 1 c .. (D) Since. (3). (D) sin πz 2 ∫ ( z − 1)( z − 2) dz c .. = ∫ [( t 2 + 2 t + 1) + i( 3t 2 + 4 t + 1)](1 + 3i) dt Or 1 dz. we get ∫ ( z − z 2 ) dz = ∫0( e Taking f ( z) = e 2 z . the singular point z = 2 lies outside z −2 the circle z = 15.

3! = 2πif (2) − 2πif (1) since. (D) f ( 3) = f ( 3) = ∫ z2 z3 (−4) + (12) + ..c s Taylor series is Hence by Cauchy’s theorem— ⇒ f (1) = f ′( z) = singular point of c ⇒ 3z 2 + 7 z + 1 ∫ z − 3 dz ... f ( z) = −1 + 2( z − z 2 + z 3 . φ ( z) = 3z 2 + 7 z + 1 ⇒ −1 4 + f ′( z o) = 2πiφ ′( z o) and f ′′( z o) = 2πi φ ′′( z o) 1 2 ... f (1) = 0 2 f ′( z) = ⇒ ( z + 1) 2 f ′′( z) = f ′′′( z) = −4 ( z − 1) 3 12 ( z + 1) 4 ⇒ ⇒ f ′(0) = 2.e.. f ( z) = sin πz 2 ⇒ f (2) = sin 4π = 0 and f (1) = sin π = 0 16.. (C) The point (1 − i) lies within circle z = 2 ( . the E O distance of 1 − i i. since zo = 3 is the only c 17. f ′′′ ⎜ ⎟ = − 2 ⎝4⎠ Taylor series is given by f ( z) = f ( z 0 ) + ( z − z 0 ) f ′( z 0 ) + ( z − z0 ) 2 f ′′( z 0 ) 2! + f ′′′(0) = 12. and so on. e in g n 18. o D Let φ ( z) = 3z 2 + 7 z + 1 then formula by Cauchy’s 3z 2 + 7 z + 1 ∫ z − zo dz = 2πiφ ( zo) c a a f ( z o) = 2πiφ ( z o) F ⇒ r e f ( z) = f ( z 0 ) + ( z − z 0 ) f ′( z 0 ) + 3z 2 + 7 z + 1 dz = 0 z−3 integral f ( z) = = ⇒ ⇒ z −1 2 =1− z +1 z +1 f (0) = −1...... z = 2. therefore analytic everywhere within c.. Now.. Taylor series is given by ( z − z0 ) 2 f ′′( z 0 ) 2! 1 1 1 1 − ( z − 1) + 3 ( z − 1) 2 − 4 ( z − 1) 3 +. the radius of the circle).Chap 9. (A) f ( z) = sin z φ′ ( z) = 6 z + 7 and φ ′′( z) = 6 m o 1 4 about z = 1 since. or f ( z) = ( z − z0 ) 3 f ′′′( z 0 ) + K 3! ⎤ 1⎡ 1 1 1 1 − ( z − 1) + 2 ( z − 1) 2 − 3 ( z − 1) 3 + .. (B) f ( z) = 1 z +1 −1 ( z + 1) 2 ⇒ f ′(1) = 3z 2 + 7 z + 1 and it lies outside the z−3 f ′′( z) = 2 ( z + 1) 3 ⇒ f ′′(1) = 3z 2 + 7 z + 1 is z−3 f ′′′( z) = −6 ( z + 1) 4 ⇒ f ′′′(1) = − circle x 2 + y 2 = 4 i.. f ′′(0) = −4...⎥ 2⎢ 2 2 2 ⎣ ⎦ f ′( z) = cos z ⇒ ⇒ ⎛π ⎞ π 1 f ⎜ ⎟ = sin = 4 2 ⎝4⎠ ⎛π ⎞ 1 f ′⎜ ⎟ = 2 ⎝4⎠ f ′′( z) = − sin z ⇒ ⎛π ⎞ 1 f ′′ ⎜ ⎟ = − 2 ⎝4⎠ f ′′′( z) = − cos z ⇒ ⎛π ⎞ 1 and so on..5 = Complex variables sin πz 2 sin πz 2 dz dz − ∫ ∫ z −2 z −1 c c 533 f ( z) = f ( z 0 ) + ( z − z 0 ) f ′( z 0 ) + ( z − z0 ) 2 f ′′( z 0 ) + 2! ( z − z0 ) 3 f ′′′( z 0 ) + . . 2 22 2 2 f ′(1 − i) = 2πi[ 6(1 − i) + 7 ] = 2π (5 + 13i) 19.e.) 1 ⎛ cos nz cos nz ⎞ ⎜ ⎟ dz − 4πi ∫ ⎝ z − 1 z +1 ⎠ c Or I = 20. 1) from the origin is 2 which is less than 2.. (1.. 2! 3! f ( z) = −1 + z(2) + about z = π 4 ( z − z0 ) 3 f ′′′( z 0 ) + . (D) Let.. (C) f ( z) = 3 and so on. 8 ⎛ −1 ⎞ ( z − 1) 2 ⎛ 1 ⎞ ( z − 1) 3 ⎛ 3 ⎞ 1 ⎜ ⎟+ ⎜− ⎟+K + ( z − 1) ⎜ ⎟ + 2 2! ⎝4⎠ 3! ⎝ 8 ⎠ ⎝4⎠ 21. 3! ... I = 1 2πi about z = 0 1 ∫ z 2 − 1 cos πz dz c ⎛ 1 1 1 ⎞ = ∫ ⎜ z − 1 − z + 1 ⎟ cos πz dz 2 ⋅ 2πi c ⎝ ⎠ = −1 + 2 z − 2 z 2 + 2 z 3..

(B) z < 1.) ⎢1 + + 2⎣ 2 4 8 ⎦ f ( z) = 1 3 7 15 3 + z + z2 + z +K 2 4 8 16 f ( z) = [1 − (1 + z)]−2 Since.⎥ ⎢1 − − 2 6 24 120 4 36 6 24 8 8 16 ⎦ z ⎣ or f ( z) = 1 z2 ⎡ ⎛1⎞ ⎛ 1 1⎞ 2 ⎢1 − z ⎜ ⎟ + z ⎜− + ⎟.⎥ 4⎠ 2!⎝ 4⎠ 3! ⎝ 4⎠ 2 ⎣ ⎝ ⎢ ⎥ ⎦ f ( z) = f ( z) = 1 3 7 + + +K z2 z3 z4 z⎞ 1 1 1⎛ − = − ⎜1 − ⎟ z −2 z −1 2⎝ 2⎠ 25.) 2 2 1 = (−2 u − 2 u3 − .H..534 Complex variables ⎛ π⎞ ⎜z − ⎟ ⎛ 1 π⎞ 1 4⎠ ⎝ f ( z) = + ⎜z − ⎟ + 2! 4⎠ 2 2 ⎝ 2 = ⎛ 1 ⎞ ⎟ ⎜− ⎜ 2 ⎟ ⎠ ⎝ ⎛ π⎞ ⎜z − ⎟ 4⎠ ⎝ + 3! ⎛ 1 ⎞ ⎟ ⎜− ⎜ 2 ⎟ +K ⎠ ⎝ 2 3 ⎤ ⎛ 1 ⎡ 1 ⎛ π⎞ 1 ⎛ π⎞ π⎞ ⎢1 + ⎜ z − ⎟ − ⎜ z − ⎟ − ⎜ z − ⎟ −...(1) = − ( z − 1)( z − 2) z − 2 z − 1 and E O −1 o D ⎞ 1⎛ 1 1 1 ⎜1 + + 2 + 3 + K⎟ z ⎝ z z z ⎠ a a −1 ⎤ 1⎡ z z2 z3 1 −1 ⎛ z⎞ ⎜1 − ⎟ = − ⎢1 + + + + K⎥ = 2⎣ 2 4 9 2⎠ z −2 2 ⎝ ⎦ F equation (1) gives— f ( z) = − ⎞ 1⎛ ⎞ 1⎛ z z z 1 1 1 ⎜1 + + + + . by binomial theorem. (B) Here f ( z) = 1 1 1 1 = − + z( z − 1)( z − 2) 2 z z − 1 2( z − 2) 1 z( e z − 1) 1 ⎡ ⎤ z2 z3 z4 + + + K − 1⎥ z⎢1 + z + 2 ! 3! 4 ! ⎣ ⎦ 1 ⎞ ⎛ z z2 z3 + +K ⎟ z 2 ⎜1 + + ⎟ ⎜ 2 ! 3! 4 ! ⎠ ⎝ −1 = 1 z2 2 3 4 ⎞ ⎛ ⎜1 + z + z + z + z + K⎟ ⎟ ⎜ 2 6 24 120 ⎠ ⎝ = 1 z2 ⎡ ⎛ z z2 z3 ⎞ z4 ⎟ ⎢1 − ⎜ + + + ⎜ 2 6 24 120 + K⎟ ⎢ ⎝ ⎠ ⎣ ⎞ ⎛ z z2 z3 ⎟ +⎜ + ⎜ 2 6 + 24 + K⎟ ⎠ ⎝ = 2 ⎞ ⎛ z z2 z3 ⎟ −⎜ + ⎜ 2 6 + 24 + K⎟ ⎠ ⎝ 3 1⎡ z z z! z" z z" z! z" z! z" z" ⎤ − − + + + + − − − ... we get 26..5 −1 + (1 − z) −1 ⎤ 1⎡ z z2 z3 + + K⎥ + (1 + z + z 2 + z 3 + .c s z = u + 1 and u < 1 1 1 1 1 = − + z( z − 1)( z − 2) 2 z z − 1 2( z − 2) ⇒ n 23.⎟ z ⎝ z z z ⎠ Laurent’s series is given by f ( z) = Required Laurent’s series is f ( z) = −( z − 1) −1 − ( z − 1) − ( z − 1) 3 − ( z − 1) 5 − K 27. =− 1 1 = z 2 [1 − (1 + z)]2 22..S. 1 + z < 1. (C) e in 1 1 [1 − u + u2 − u3 + ..... z > 1 ⇒ 1 1 1 ..⎟ − ⎜1 + + 2 + 3 + .⎟ z⎝ z z z z⎝ z z z ⎠ ⎠ r e 1 1 1 1 1 − + = (1 + u) −1 − u−1 − (1 − u) −1 2( u + 1) u 2( u − 1) 2 2 = 1 < 1 and z < 2 z ⇒ 1 1 1⎛ 1⎞ = = ⎜1 − ⎟ ⎛ 1⎞ z ⎝ z −1 z⎠ z ⎜1 − ⎟ z⎠ ⎝ = = m o . so by expanding R.. ⎝2 ⎠ ⎝ 6 4⎠ ⎣ ..⎟ − ⎜1 + + 2 + 3 + K⎟ ⎜ ⎟ z 2⎝ 2 4 9 z z z ⎝ ⎠ ⎠ 2 2 <1 z 1 1⎛ 1⎞ = ⎜1 − ⎟ z −1 z ⎝ z⎠ and −1 = 1 1 1 1 3 − z − z2 − z −K 2 4 8 18 1 1 < <1 z 2 ⇒ ⇒ 1 <1 z ⎞ 1⎛ 1 1 1 ⎜1 + + 2 + 3 + K⎟ 2⎝ z z z ⎠ 1 1⎛ 2⎞ = ⎜1 − ⎟ z −2 z ⎝ z⎠ −1 = ⎞ 1⎛ 2 4 8 ⎜1 + + 2 + 3 + .. (D) Let f ( z) = z −2 = ⎞ 1 ⎛1 3 7 ⎜ + 2 + 3 + K⎟ z ⎝z z z ⎠ ⇒ 3 Chap 9.. For z − 1 < 1 Let z − 1 = u f ( z) = 1 + 2(1 + z) + 3(1 + z) 2 + 4(1 + z) 3 + K + ( n + 1)(1 + z) + K ∞ or f ( z) = z −2 = 1 + ∑ ( n + 1)( z + 1) n n =1 Since..... ] − u−1 − (1 + u + u2 + u3 + ....) − u−1 = −u − u3 − u5 − K − u−1 2 g n z <1 2 ⎞ 1⎛ ⎞ 1⎛ 2 4 98 1 1 1 ⎜1 + + 2 + 3 + . (B) Let f ( z) = = = 3 or f ( z) = K−z −4 − z −2 − z −1 − 24. (D) Since.

e.. z ≤ θ ≤ 2π z 1 1 i.. Residue at z = 0 is 1 − 2z 1 = lim zf ( z) = lim = z →0 z →0 (1 − z)( z − 2) 2 ⎤ ⎛ 1 1 1 1 1⎞ ⎟ + K⎥ + z 4 ⎜− + + − + ⎝ 120 36 24 8 16 ⎠ ⎦ = ⎤ ⎛ 1 ⎞ 1 ⎡ 1 1 2 ⎟ + K⎥ z+ z + 0 z 3 + z 4 ⎜− 2 ⎢1 − 2 12 z ⎣ ⎝ 720 ⎠ ⎦ and Residue at z = 1 is 2z − 1 = lim ( z − 1) f ( z) = lim = −1 z →1 z →1 z( z − 2) Required Laurent’s series is f ( z) = 1 1 1 1 2 − + + 0. 1. ( z − z o ) m f ( z) ( m − 1) ! z →z dz m −1 a a 3 1 d lim ( 4 − 1) ! z →0 dz 3 F ⎡ ⎢z4 ⎢ ⎣ ⎛ 1 − e2 z ⎞ ⎤ ⎟ ⋅⎜ ⎜ z4 ⎟⎥ ⎝ ⎠⎥ ⎦ −1 1 d3 = lim (1 − e 2 z ) = lim 8 e cz 3 ! z →0 dz 3 3 ! z →0 = e in π is 2 2 ⎤ d ⎡⎛ π⎞ d ⎢ ⎜ z − ⎟ f ( z) ⎥ = lim = lim ( z cos z) π dz ⎢ ⎝ π dz 2⎠ ⎥ ⎣ ⎦ z →2 z→ 2 Now.. = by Cauchy’s residue theorem ⎛ π ⎞ ∫ f ( z) dz = 2πi × ⎜ Residue at z = 2 ⎟ ⎝ ⎠ c 1 5 3 21 5 z− z + z K 4 16 64 29. which lies within the circle z = 1 −8 o −8 −4 (e ) = = 6 6 3 ∫ f ( z) dz = 2πi(residue at z = 0) c 1 30... 2 since 0 and 1 lie within c and c = 2 does not inside c. Poles of f ( z) are at z = 0.e. z − z +K z 2 2 z 12 720 28.(1) c Now. ⎝ 24 6 8 ⎠ ∫ f ( z) dz = 2πi[sum of residues at z = 0 and at z = 1]. (B) Let z = e iθ 1 1 i.. (A) Since. 1 ∫ f ( z) dz = 2πi × 6 = 3 πi and cos θ = 1 2 ⎛ 1⎞ ⎜z + ⎟ z⎠ ⎝ ⇒ dθ = −idz .5 Complex variables ⎛ 1 1 1⎞ + z 3 ⎜− + − ⎟. f ( z) = equation (1) gives ⎛ 1 ⎞ ∫ f ( z) = 2πi × ⎜− 2 − 1⎟ = − 3πi ⎝ ⎠ c z ( z 2 + 1)( z 2 + 4) z = − 2 2 3( z + 1) 3( z + 4) f ( z) = = ⇒ |z 2 | < 1 z z (1 + z 2 ) −1 − 3 12 2 ⎞ ⎛ ⎜1 + z ⎟ ⎜ 4⎟ ⎠ ⎝ −1 g n E O o D 1 d m −1 lim. z 6 . z z (1 − z 2 + z 4 − . (D) f ( z) = z | z| < 1 535 = lim [cos z − z sin z ] = − z→ π 2 π 2 ⎛ π⎞ ∫ f ( z) dz = 2πi × ⎜− 2 ⎟ = −π 2 i ⎝ ⎠ c ⎛ ⎞ 1 1 1 ⎟ 33. (B) Let f ( z) = m o . (B) Put z = 0 + t . f ( z) = z cos z = t cos =t− Now. (C) f ( z) = z 2 e1 z = z 2 ⎜1 + + 2 + 3 +K z 2 !z 3! z ⎝ ⎠ 1 1 = z2 + z2 + + +K 2 6z The only pole of f ( z) is at z = 0.c s order 2.. − 2 t 31..Chap 9. residue of f ( z) at z = 0 is the coefficient of 1 ⎞ 1 ⎛ 1 1 1 1 ⎟ = t ⎜1 − 2 + 4 −K t 2! t 4! t ⎝ ⎠ c 1 1 + −K 2 t 24 t 3 Residue of f ( z) at z = 0 is the coefficient of 34.) − 3 12 or f ( z) = z cos z π of 2 then f ( z) has a pole at z = 2 ⎛ π⎞ ⎜z − ⎟ 2⎠ ⎝ 32. Residue at z = 1 − e2 z then f ( z) has a pole at z = 0 of z4 Residue of f ( z) at z = 0 = r e 2 4 ⎛ ⎞ ⎜1 − z + z − K⎟ ⎜ ⎟ 4 16 ⎝ ⎠ order 4.

z = ± ib.. 5.. 2. 1 + z6 = 0 ∫ f ( z) dz = 2πi(Residue at z = −2 + ⇒ 3) z = (−1) π 6 = e i ( 2 n + 1 ) π 6 c where n = 0. Here only z = ia and ∫ f ( z) dz = 2πi o D a a c (sum of residues at z = ia and z = ib) Residue at z = ia. (C) Let I = ∫ 1 z2 + 4z + 1 c is the contour containing semi circle r of radius R f ( z) has poles at z = − 2 + 3. The poles are z = ± ia. 1⎛ 1⎞ 2 + ⎜z + ⎟ z⎠ 2⎝ Now when R → ∞.5 dz 6 = ∫ f ( z) dz c 1+ z c 36. 1. ie iθdθ R5 1 + e6 iθ R6 ∫ f ( z) dz → 0 r ∞ (1) → ∫ 0 ax 2π = 1 + x6 3 π ******** . 3. z = −2 + 3 lies inside the circle c : z = 1 For poles of f ( z). ∫ b( z) dz = 0 r c: z =1 ∞ x 2 π ∫ ( x 2 + a 2 )( x 2 + b2 ) dz = a + b −∞ dz = − 2i∫ 2 c z + 4z + 1 Let f ( z) = Chap 9. 4. (C) I = ∫ − 3+i .536 Complex variables 2π dθ ∫ 2 + cos θ = ∫ 0 c −idz z .c s 1 − 3i = = 12 i 3i(1 + 3 i) 1 2 2 m o 3+i lie in the contour 2 Residue at z = 2π 35. residue at z = −2 + 3 Only poles = lim z →−2 + 3 = lim z →−2 + 3 ( z + 2 − 3) f ( z) 1 ( z + 2 + 3) ∫ f ( z) dz = 2πi × 2 1 c = 1 πi 3 dθ πi 2π ∫ 2 + cos θ = −2 i × 3 = 3 0 E O where c is be semi circle r with segment on real axis from −R to R.. 2 + 3+i 2 1 = ( z1 − z 2 )( z1 − z 3)( z1 − z 4 )( z1 − z 5)( z1 − z6 ) 2 3 = 3 z = where R → ∞. F Residue at z = i is Residue at z = = 1 3i(1 − 3i) c = Now r π Now ∫ f ( z) dz = ∫ ( R 2 e2 0 r ∫ f ( z) dz + ∫ f ( z) dz = r −R ie 2 iθiRe iθdθ + a 2 )( R 2 e 2 iθ + b2 ) iθ e 3iθ dθ R = ∫ ⎛ a 2 ⎞ ⎛ 2 iθ b2 ⎞ 0 ⎜ 2 iθ ⎟ ⎟⎜ ⎜ e + R2 ⎟ ⎜ e + R2 ⎟ ⎠ ⎠⎝ ⎝ 2π .(1) 3 ∫ f ( z) dz c π iθ iRe dθ = 1 + R6 e6 iθ 0 =∫ π ∫ 0 −R 2πi π = 2 2 ( a − b) = 2i (a − b ) a+b ∫ f ( z) dz −R R 2 ∫ f ( z) dz = ∫ f ( z) dz + ∫ f ( z) dz R 2πi 2π (1 − 3i + 1 + 3i + 2 i) = 12 i 3 Residue at z = ib R 1 + 3i 12 i r or z −b = lim ( z − ib) = z →ib ( z − ia)( z + ia)( z + ib)( z − ib) 2 i( a 2 − b2 ) = 1 6i 1 + 3i is 12 i ∫ f ( z) dz = ∫ f ( z) dz + z2 a = lim ( z − ia) = z →ia ( z − ia)( z − ia)( z 2 + b2 ) 2 i( a 2 − b2 ) c r e e in g n z dz = ∫ f ( z) dz ( z + a )( z 2 + b2 ) c c 2 z = ib lie within the contour c . −2 − 3 out of these only and segment from −R to R. i. 6 Now.

5 Complex variables 537 m o r e .Chap 9.c s e in g n E O o D F a a .